Fundamental parameters and abundance analysis of the components in the SB2 system HD 60803. Issue 1 (8th November 2021) - Ryabchikova, T; Zvyagintsev, S; Tkachenko, A; Tsymbal, V; Pakhomov, Yu; Semenko, E
ABSTRACT: We perform a detailed spectroscopic study of the SB2 system HD 60803 based on high-resolution spectra obtained with different spectrographs. The analysis was done using two independent methods: a) direct modelling of the observed binary spectrum by a sum of synthetic spectra with a varying set of free parameters and minimizing the difference between the observed and theoretical spectra; and b) spectrum disentangling and independent modelling of the individual components. When applied to binary spectra from different spectrographs, both methods converge to a consistent solution for the fundamental parameters of the HD 60803 components: T eff = 6 055 ± 70 K, log  g = 4.08 ± 0.12, ξt = 1.45 ± 0.18 km s −1, [M/H] = 0.03 ± 0.06 (primary), and T eff = 6 069 ± 70 K, log  g = 4.14 ± 0.09, ξt = 1.48 ± 0.18 km s −1, [M/H] = 0.03 ± 0.06 (secondary). Differential abundance analysis of the components does not reveal any significant difference in their chemical composition. Apart from Li, both components have solar atmospheric abundances. The Li abundance exceeds the solar value by ∼2 dex, but it agrees with the Li abundance in main-sequence late-F-type stars. Relative-to-solar abundances in both components slightly correlate with the condensation temperature in the same way as that found in the solar analogues with/without detected giant planets. The estimated age of the system is 5.5 ± 0.5 Gyr.